From class waivers to precision medicine in paediatric oncology - Pearson, Andrew D. J.; Pfister, Stefan; Jones, David T. W. (The lancet. Oncology, 2017)
Summary New drugs are crucially needed for children with cancer. The European Paediatric Regulation facilitates paediatric class waivers for drugs developed for diseases only occurring in adults. In this Review, we retrospectively searched oncology drugs that were class waivered between June, 2012, and June, 2015. 147 oncology class waivers were confirmed for 89 drugs. Mechanisms of action were then assessed as potential paediatric therapeutic targets by both a literature search and an expert review. 48 (54%) of the 89 class-waivered drugs had a mechanisms of action warranting paediatric development. Two (2%) class-waivered drugs were considered not relevant and 16 (18%) required further data. In light of these results, we propose five initiatives: an aggregated database of paediatric biological tumour drug targets; molecular profiling of all paediatric tumours at diagnosis and relapse; a joint academic-pharmaceutical industry preclinical platform to help analyse the activity of new drugs (Innovative Therapy for Children with Cancer Paediatric Preclinical Proof-of-Concept Platform); paediatric strategy forums; and the suppression of article 11b of the European Paediatric Regulation, which allows product-specific waivers on the grounds that the associated condition does not occur in children. These initiatives and a mechanism of action-based approach to drug development will accelerate the delivery of new therapeutic drugs for front-line therapy for those children who have unmet medical needs.